Synchronization of single-phase inverter with grid connection system by using enhanced phase locked loop method - Abdullah, Muhammad Zulkarnain (2018)
This project is describing the synchronization technique for synchronization of inverter voltage output with grid or Alternating Current (AC) voltage. With the synchronization technique, renewable energy that has been generated through multiple sources can be used in the grid and the lack of energy or the dependence on fossil fuels can be automatically minimized. In order to fulfill the demands, grid synchronization techniques play a vital and critical role in the control of single-phase system. In this project, for the purposes of synchronization in diverse fields, a Phase Locked Loop (PLL) has been widely used as a control system. Most importantly, this control system is also used in synchronizing the inverter output voltage with grid voltage. The PLL has been a subject of great interest due to its significant and many projects as well as their improvements have been recommended for its execution. In order to meet the objectives, Arduino is used to play as a major part on processing the grid value and at the same time generating the desired Pulse with Modulation (PWM) for the inverter to make the synchronization happened. This project presents an Enhanced Phase Locked Loop (EPLL) for single-phase inverter which generates the orthogonal voltage that is merely the same with AC source or grid system. As a result, it is proven that EPLL has significantly proved its topology as an adaptive filter that filtering phase angle to the desired angle that can makes the synchronization takes place.